Co-Designing Technology for Aging in Place: A Systematic Review - Sumner, Jennifer; Chong, Lin Siew; Bundele, Anjali; Wei Lim, Yee (The Gerontologist, 2021)
Abstract Background and Objectives There is a growing interest to involve older adults in the co-design of technology to maintain their well-being and independence. What remains unknown is whether the beneficial effects of co-designed solutions are greater than those reported for non co-designed solutions. The aim of this study was to evaluate the effects and experiences of co-designed technology that support older adults to age in place. Research Design and Methods We conducted a systematic review to (a) investigate the health and well-being outcomes of co-designed technology for older adults (≥60 years), (b) identify co-design approaches and contexts where they are applied, and (c) identify barriers and facilitators of the co-design process with older adults. Searches were conducted in MEDLINE, EMBASE, CINAHL, Science Citation Index (Web of Science), Scopus, OpenGrey, and Business Source Premiere. Results We identified 14,649 articles and included 34 projects. Four projects reported health and well-being outcomes; the effects were inconsistent. Co-design processes varied greatly and in their intensity of older adult involvement. Common facilitators of and barriers to co-design included the building of relationships between stakeholders, stakeholder knowledge of problems and solutions, and expertise in the co-design methodology. Discussion and Implications The effect of co-designed technology on health and well-being was rarely studied and it was difficult to ascertain its impact. Future co-design efforts need to address barriers unique to older adults. Evaluation of the impact of co-designed technologies is needed and standardization of the definition of co-design would be helpful to researchers and designers.